Chapter Wine preferences based on intrinsic attributes: A tasting experiment in Alto Adige/Südtirol province - Fabbris, Luigi (Proceedings e report, 2021)
Different methods have been developed by researchers in modelling wine consumers purchase behaviour. The quality of a food product is described by a set of characteristics ascribable to the intrinsic and extrinsic product attributes (Olson and Jacoby, 1972). Price, brand, region of origin, grapes and gained awards are the key extrinsic attributes and physical characteristics of the wine such as taste and flavour are intrinsic attributes. This paper addresses the problem of measuring the intrinsic attributes that characterise the wine, based on specific characteristics and the impact on consumers in terms of preferences. To this end, a fractional factorial experiment held on a selection of white wines of the Alto Adige/Südtirol province in Italy. The sensorial experiment involved a voluntary sample of 33 mild wine consumers and concerned 6 grape varieties typical of that territory. For each variety, two producing cellars were selected for a total of 12 evaluated wines. The experiment followed a double-blind administration procedure to the sample and a paper questionnaire was used to elicit the consumers' opinions on the tasted wines. The results show that intrinsic attributes, such as taste-olfactory intensity, harmony and olfactory complexity, are the drivers used in combination by consumers to rank wines in order of preference.